Pemberdayaan Ibu Berbasis Peer Support Groups untuk Meningkatkan Perilaku Pemeriksaan Payudara Sendiri: Empowering Mothers Based on Peer Support Groups to Improve Breast Self-Examination Behavior - Br Pinem, Jenaika; Puspitasari, Yenny (Chakra Brahmanda Lentera Institute, 2025)
Pulmonary tuberculosis patients often face issues of non-compliance with treatment, driven by boredom and the decision to stop therapy due to the lengthy treatment duration and feelings of persistent illness. This community service activity aimed to enhance the skills and behaviors associated with breast self-examination (BSE) among the community through health education based on peer group support. The community service program was conducted from August 26, 2024, to September 7, 2024, within the working area of Barusjahe Public Health Center, Karo Regency. The program was implemented in three phases: preparation, execution, and evaluation. A total of 15 participants were involved. The assessment of breast self-examination behavior was carried out using a Likert-scale-based questionnaire, with results categorized into three ordinal data scales: Good Behavior, Moderate Behavior, and Poor Behavior. Data collected were analyzed using statistical tests with SPSS software. The results indicated a significant improvement in BSE skills and behavior after delivering health education based on peer group support. Health education based on peer group support effectively enhances breast self-examination behavior..